The Molecular Tumor Board Portal supports clinical decisions and automated reporting for precision oncology - Tamborero, David; Dienstmann, Rodrigo; Rachid, Maan Haj; Boekel, Jorrit; Lopez-Fernandez, Adria; Jonsson, Markus; Razzak, Ali; Braña, Irene; De Petris, Luigi; Yachnin, Jeffrey; Baird, Richard D.; Loriot, Yohann; et al. (Nature cancer, 2022)
There is a growing need for systems that efficiently support the work of medical teams at the precision-oncology point of care. Here, we present the implementation of the Molecular Tumor Board Portal (MTBP), an academic clinical decision support system developed under the umbrella of Cancer Core Europe that creates a unified legal, scientific and technological platform to share and harness next-generation sequencing data. Automating the interpretation and reporting of sequencing results decrease the need for time-consuming manual procedures that are prone to errors. The adoption of an expert-agreed process to systematically link tumor molecular profiles with clinical actions promotes consistent decision-making and structured data capture across the connected centers. The use of information-rich patient reports with interactive content facilitates collaborative discussion of complex cases during virtual molecular tumor board meetings. Overall, streamlined digital systems like the MTBP are crucial to better address the challenges brought by precision oncology and accelerate the use of emerging biomarkers.